Impact of Organizational Learning Culture on Instructor Innovative Behavior of Private Higher Education Institutions in Sichuan Province, China - Shi , Zhenggang; Na Srito, Pavinee (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
the research found that: 1) The distribution of demographic characteristics of respondents, the majority of respondent were female of 62 %, their ages between 31-40 years old of 35.6%, education level graduate master’s degree, of 56.8%, teaching experience: < 5 of 28.5%, and academic title associate professor, 24.7%. 2) There are various factors such as organizational learning culture, knowledge sharing that have the impact on instructor innovative behavior. 3) In this regard, this study has been designed in order to find out the impact of organizational learning culture, on instructor innovative behavior, via knowledge sharing in the mediating role that have the significant impact. Furthermore, it was found out that the mediating impact of knowledge sharing factors is significant in the relationship of all the independent and dependent variables.